Analysis of Edible coating Based on Corn Starch and Ginger Extract (Zingiber officinale) as Active Packaging on Cherry Tomatoes (Solanum lycopersicum var. cerasiforme) - Silvia, Deli; Muryeti, Muryeti; Zahra, Meida Aminatu (Seminar Nasional Lahan Suboptimal, 2024)
Silvia, D., Muryeti, M., & Zahra, M. A. (2024). Analysis of edible coating based on corn starch and ginger extract (Zingiber officinale) as active packaging on cherry tomatoes (Solanum Lycopersicum Var. Cerasiforme). In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-12 Tahun 2024, Palembang 21 Oktober 2024. (pp. 389–397). Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Research has been conducted on the analysis of the application of active packaging in the form of edible coatings made from corn starch and ginger extract to extend the shelf life of cherry tomatoes. Cherry tomato fruit is part of horticultural commodities that are easily damaged after post-harvest. The level of horticultural products such as fruits is influenced by fruit gas activity (diffusion) through the surface of the fruit skin. This diffusion will be inhibited by the skin which is easily decomposed during the post-harvest process. One way to extend the shelf life is to coat the fruit skin with an edible coating. Edible coatings made from corn starch (3% and 6%), Ginger extract (3, 6 and 9%), 1% pectin and 1% glycerol were applied to cherry tomatoes at room temperature. This study aimed to analyze the effectiveness of corn starch and ginger extract as active packaging that can extend the shelf life of cherry tomatoes. Tests carried out in the form of total soluble solids, pH, Vitamin C content and Organoleptic with color, texture and aroma attributes. Data were analyzed using SPSS ANOVA two factorial DMRT (Duncan Multiple Range Test) as a follow-up test. The results obtained were processed by two-factorial ANOVA with. The results showed that 3% corn starch concentration had an effect on the weight loss test of tomato fruit and 6% ginger extract concentration had an effect on the acidity test of cherry tomato fruit The test results show that the application of edible coatings from corn starch and ginger extract has the potential to extend the shelf life of cherry tomatoes through changes in the pH value of the fruit.